1992
DOI: 10.1111/j.1600-9657.1992.tb00229.x
|View full text |Cite
|
Sign up to set email alerts
|

Induced periapical lesions in ferret canines: histologic and radiographic evaluation

Abstract: Ferrets have been utilized in endodontic research to study periapical responses. However, various aspects of induction and healing of periapical pathosis in ferrets are unclear. This study evaluated the radiographic and histopathologic features of induced periapical lesions. Periapical pathosis was consistently produced in 8 canines of 2 ferrets by extirpating the pulp, leaving the cavities open for a week, then sealing for 12 weeks. The resulting lesions were evaluated radiographically every two weeks. The an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 27 publications
2
18
0
1
Order By: Relevance
“…Studies in experimental ferrets showed that pulp exposure led to infection, inflammation, and necrosis of the pulp followed by formation of radiographically detectable periapical lesions as early as 4-weeks after pulp exposure. 9 In the present study, more than 50 % (9 of 15) of all fractured teeth were confirmed to have resulted in exposure of the pulp chamber. Worn and fractured teeth without pulp exposure may also be at risk of endodontic disease.…”
Section: Figurementioning
confidence: 55%
“…Studies in experimental ferrets showed that pulp exposure led to infection, inflammation, and necrosis of the pulp followed by formation of radiographically detectable periapical lesions as early as 4-weeks after pulp exposure. 9 In the present study, more than 50 % (9 of 15) of all fractured teeth were confirmed to have resulted in exposure of the pulp chamber. Worn and fractured teeth without pulp exposure may also be at risk of endodontic disease.…”
Section: Figurementioning
confidence: 55%
“…Pulp exposure is considered painful and ferrets were described in experimental studies to develop endodontic disease with associated radiographic signs early after pulp exposure (Fouad et al . ). Interestingly, despite the frequent occurence of (in many cases long‐standing) pulp exposure because of crown‐, crown‐root and root fractures in this study, radiographic signs of endodontic disease (Fiani & Arzi ) were only observed in approximately 30% of the cases.…”
Section: Discussionmentioning
confidence: 97%
“…However, the kinetics of the healing of the inflamed tissues, ie, regeneration of bone, is less well understood. Most information known is at histologic and cellular level concerning periapical healing and bone regeneration after surgical procedures or root canal treatment (1722). There has been no study on the possible existence of stem cells in the apical inflamed tissues in terms of their role in regulation of inflammation and healing.…”
Section: Discussionmentioning
confidence: 99%